Evaluasi Implementasi Program E-Warong KUBE-PKH di Kabupaten Sukoharjo (Studi Kasus di Kecamatan Mojolaban) - Anisa Fauziyah Hanum; Retno Suryawati (Jurnal Mahasiswa Wacana Publik, 2021)
This study aims to evaluate the implementation of the KUBE PKH E-Warong Program in Mojolaban District, Sukoharjo Regency. This study method is descriptive with a qualitative approach using interview data collection techniques, observation and documentation. The technique of collecting informants in this study was using purposive sampling technique. This study was analyzed using data analysis techniques Miles and Huberman. The results showed that the implementation of the E-Warong Kube PKH program in Mojolaban Subdistrict, Sukoharjo Regency was carried out through 4 stages, namely socialization, Establishment of E-Warong and Kube, Arrangements for the supply of goods to E-Warong, Monitoring and Evaluation. In the compliance aspect, almost all implementations comply with the rules even though there are still some implementations that have not been optimal at the E-Warong and Kube formation stages because not all E-Warong Kube in Mojolaban District, Sukoharjo Regency have developed, and there is still unclear distribution of sales profits between E-Warong managers. Warong Kube in Mojolaban District, Sukoharjo Regency. Of the factors that influence implementation, there are supporting and inhibiting factors in the implementation of the E-Warong Kube PKH Program in Mojolaban District, Sukoharjo Regency. Supporting factors can be seen from the indicators of the number of actors involved, clarity of objectives, complexity of programs, and participation of all government units. Meanwhile, the inhibiting factor is seen from the uncontrollable factors that influence implementation.